SPEAKING PROJECT BASED-LEARNING (SPjBL) AS AN INNOVATIVE LEARNING IN PROMOTING STUDENTS’ SPEAKING SKILL AT SENIOR HIGH SCHOOL CONTEXT - Abdul, Nurdevi Bte; Daddi, Herlina; Kamariah, A. (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
This study concerns with the implementation of Project Based-Learning in promoting students’ speaking skill at senior high school context. It focuses on finding out students’ improvement in Speaking through Project-Based Learning (PjBL). It also described the teacher’s way in implementing PjBL, and students’ response. Since the learning activities focused on speaking materials, so the terms of Speaking Project-Based Learning (SPjBL) was used in this study. Classroom action research for three cycles was applied in this research. Each cycle consisted of four phases, namely planning, action, observation, and reflection. Students’ activity during the lesson running was observed and recorded. At the end of each cycle, the researchers conducted speaking test to know students’ improvement and interview was administered to students for knowing their response on SPjBL. The research findings indicates that the students’ speaking skill improve from cycle one to cycle two, and from cycle two to cycle three. It is proven by calculating students’ test score that cycle one is 77.85, cycle two is 82.61, and cycle three is 83.88. The students give positive response of the use of SPjBL in improving their speaking skill. Therefore, it can be concluded that, the SPjBL as an innovative learning could improve students’ speaking skill at school context. This study gives two implications on theoretical and practical in terms of applying the appropriate learning approach or method enhance students’ skill and achievement.